Community coalitions’ navigation of policies to address the opioid epidemic: insights from qualitative interviews in four states - Elizabeth N Kinnard; Ann Scheck McAlearney; Timothy Hunt; Ramona G Olvera; Allyson G Cogan; Mary Bartkus; Shoshana N Benjamin; Jill Davis; Lisa A Frazier; Brandy F Henry; Hallie Mattingly; Dean Rivera; et al. (BMJ Public Health)
Introduction The opioid epidemic in the USA presents a multifaceted challenge regulated by a patchwork of federal, state and local policies. In some communities, cross-sector coalitions navigate this complex policy environment to address the epidemic. However, limited research has explored these public health-oriented community coalitions and their interactions with the policy landscape. This study explores how cross-sector public health-oriented community coalition members perceive and navigate the multidimensional policy landscapes to address the opioid epidemic.Methods Using data from 304 semistructured HEALing Communities Study coalition member interviews conducted April–June 2021 in 67 communities in Kentucky, New York, Massachusetts and Ohio, we inductively analysed participants’ discussions of opioid-related policies to characterise themes and subthemes.Results We describe two themes where coalitions and policy intersect: policy landscape barriers and navigation and mitigation strategies to address policy barriers. Participants revealed community misunderstandings and lack of knowledge of opioid-related policies. Furthermore, participants shared how these policies often hindered coalitions’ initiatives to address substance use. Nevertheless, community coalitions functioned despite these policy challenges through knowledge sharing, innovation and policy advocacy.Conclusions Cross-sector public health-oriented community coalitions serve a vital role in navigating the complexities of the multidimensional policy landscape regulating substance use services. Insights from these findings may encourage policy-makers to support community coalitions in pursuing solutions to the opioid crisis and other public health crises.Trial registration number NCT04111939.